Analysis of Cross-Cultural Communication Barriers (Case Study of Husband and Wife of Sasak Tribe and Samawa Tribe in Poto Tano District, West Sumbawa Regency) - Riski Agustini; Lalu Ahmad Taubih; Firdaus AM (Journal of Social Growth and Development Studies, 2025)
This research is entitled "Analysis of Cross-Cultural Communication Barriers (Case Study of Sasak and Samawa Tribe Husband and Wife Couples in Jembatang Kemar Hamlet, Senayan Village)". This research is motivated by the phenomenon of elopement, early marriage, and the high divorce rate in the region, which is thought to be related to intercultural communication barriers. The purpose of this research is to find out and analyse the cross-cultural communication barriers experienced by married couples from two different cultural backgrounds, namely the Sasak Tribe and the Samawa Tribe. This research uses a qualitative approach with a case study method. Data were obtained through observation, in-depth interviews, and documentation of six married couples from different ethnic groups who live in Jembatang Kemar Hamlet. The results showed that the main barriers come from language differences that cause misunderstanding, loss of meaning, and awkwardness in communication. In addition, differences in norms or habits, as well as a lack of self-confidence, also contribute to increasing the risk of small conflicts in household relationships.